Relation between occupation, gender dominance in the occupation and workplace and suicide in Sweden: a longitudinal study - Gun Johansson; Theo Bodin; Anette Linnersjö; Vladimir Carli; Gergö Hadlaczky; Nuria Matilla Santander; Bianca Blazevska (BMJ Open)
Objectives To describe the association between occupations and suicide, and to explore the effect of gender dominance in the occupation and in the workplace on the risk of suicide.Design Register-based cohort study.Participants 3 318 050 workers in Sweden in 2005 and followed up until 2010. Exclusion criteria for the study were: missing information in the occupational codes, yearly income of <100 Swedish krona, missing information of the employer, death or migration, and registered occupational code reported from more than 5 years ago.Outcome Suicides occurring during 2006–2010 identified in the cause of death register by the International Classification of Diagnoses-10 codes X60–84 and Y10–34.Results Occupations with increased suicide were life science and health professionals (OR: 2.8, 95% CI: 1.50 to 5.26) among women. In men, these were metal, machinery and related workers (OR: 1.5, 95% CI: 1.09 to 2.05) and personal and protective service workers (OR: 1.59, 95% CI: 1.14 to 2.22). In terms of gender dominance in the occupation, borderline associations with increased suicide risk were found for men in both male-dominated (OR: 1.32, 95% CI: 0.98 to 1.79) and female-dominated (OR: 1.37, 95% CI: 0.99 to 1.91) occupations. For women, borderline increased risk of suicide was found in female-dominated occupations (OR: 1.51, 95% CI: 0.95 to 2.40). Finally, men showed a borderline increased risk of suicide in female-dominated workplaces (OR: 1.31, 95% CI: 0.94 to 1.81).Conclusions This study found that women in the ‘life science and health professionals’ group and men in the ‘metal, machinery and related workers’ as well as ‘personal and protective service workers’ groups have increased incidence of suicide also when adjusting for sociodemographic characteristics, precariousness of the employment relationship, spells of unemployment, previous mental disorders and suicide attempts. Moreover, gender dominance at workplace and occupation seems to be associated with the risk of suicide among men. The results of our study are novel and are worth exploring in future qualitative studies.